Modelo Computacional para optimizar parámetros de construcción de una antena fotoconductora (PCA) (2019)
This work presents the outcome of a computational modelling, which studies the behavior of a terahertz photoconductive antenna. The parameter’s build has been changed to optimize the power and frequency of the terahertz pulse. So, the article will describe each parameter with their specific result and how it changes to find the acceptable result. The commercially accessible finite element method COMSOL Multiphysics is implemented to unravel the correlation among each parameter. The input of model will be the geometry and material of antenna. The laser will be defined between three kinds of this.